Paleoecological reconstruction of hominin-bearing middle Pliocene localities at Woranso-Mille, Ethiopia. Issue 96 (July 2016) - Curran, Sabrina C.; Haile-Selassie, Yohannes
Abstract: Woranso-Mille is a paleoanthropological site in Ethiopia sampling an important and under-represented time period in human evolution (3.8–3.6 million years ago). Specimens of cf. Australopithecus anamensis, Australopithecus afarensis, and the recently named Australopithecus deyiremeda have been recovered from this site. Using multiple habitat proxies, this study provides a paleoecological reconstruction of two fossiliferous collection areas from Woranso-Mille, Aralee Issie (ARI) and Mesgid Dora (MSD). Previous reconstructions based on faunal assemblages have pointed, due to the presence of aepycerotins, alcelaphins, and proboscideans, to the existence of open habitats as well as more closed ones, based on the occurrence of cercopithecids, giraffids, and traglephins. Results from community structure analysis (proportions of locomotor and dietary adaptations) at ARI and MSD indicated a predominance of open habitats, such as shrublands. Mesowear analysis revealed that ungulates of all dietary types (grazers, leaf and fruit browsers, and mixed feeders) were present in nearly equal proportions. Ecomorphological analyses using linear measurements of the astragalus and phalanges indicated that bovids utilizing locomotor behaviors associated with all habitat types were present, though the intermediate-cover habitat bovids were best represented in the sample (Heavy cover at ARI and Light cover at MSD). Together, these results suggest that the ARI and MSD localities were heterogeneous habitats (mosaics), likely with densely vegetated areas along a paleo-river and more open regions (woodlands, grasslands) available away from the river.